POTENSI DAN STRATEGI PENGEMBANGAN EKOWISATA BUKIT MAMAKE DI AREAL IUPHKM MUTIARA DESA SARANG TIUNG KABUPATEN KOTA BARU - Mulyadi, Sukma; Fitria, Abdi; Biyatmoko, Danang; Badaruddin, Badaruddin (Universitas Lambung Mangkurat, 2024)
The tourism potential of Bukit Mamake has increased with community participation and support from the Head of the South Kalimantan Forestry Service and the Regent of Kotabaru. This study aims to analyze the potential of Bukit Mamake ecotourism as a tourism destination and develop strategies in the development of Bukit Mamake ecotourism. The data obtained includes primary data from observation results, questionnaires, and interviews, as well as secondary data from research supporting information. The assessment uses the Guidelines for the Analysis of Areas of Operation of Natural Tourism Objects and Attractions (ADO-ODTWA) of the Director General of PHKA 2003, analyzed according to the screening criteria. Evaluation of the elements and sub-elements of each ODTWA criterion is used to classify the feasibility level of ODTWA potential for development. Data from potential tourist attractions are then assessed with a SWOT approach. Assessment followed ADO-ODTWA guidelines, with a score of 4.495 indicating average conditions and management. SWOT analysis placed Bukit Mamake in Quadrant 1 (positive; positive) with an aggressive strategy, highlighting its potential as a leading destination. Strategies include local government support for promotion, and collaboration to enhance community welfare through ticket revenue sharing, local employment, and business opportunities at the site.